Diversity-based Approach in Post Disaster Management - Deni Nurdyana Hadimin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Disasters cause marginalization, inequality and vulnerability caused by power relations, resulting in diversity in the community. This article aims to describe diversity in disasters as well as practical competence through a diversity-based approach. The research method uses a literature review with a descriptive approach to describe diversity in disasters. The results of the study concluded that diversity in disasters can be divided into several categories, namely women, the elderly, people with disabilities, children and adolescents and people with mental disorders. Diversity-based approach competence through cultural competence needs to be carried out in implementing post-disaster management interventions.